(untitled) (Journal of Economic Research & Business Administration, 2022)
This article extends research about the impact of microfinance on macroeconomic performance, including economic and financial development. Microfinance, as emphasized by the Asian Development Bank, provides financial services to the poor, thus increasing the level of consumer activity, production and entrepreneurship, making a significant contribution to the development of the economy, especially in post-crisis periods. Stable economic growth, as proved by developed and developing countries, directly depends on the activity of small and medium-sized enterprises, which stimulate the entrepreneurial activity of population and creates new jobs. However, one of the significant obstacles to the creation and development of SMEs is access to finance. The purpose of this paper is to analyze the impact of SME financing, both through microfinance organizations and through banks, on the Human Development Index, as an indicator of the development of the economy of Kazakhstan. This index is a more comprehensive indicator of a country’s development, which takes into account not only economic growth, but also the quality of life of population. The paper also discusses the relationship between SME financing and the proportion of the country’s population with incomes below the subsistence level. Thus, given the narrow focus of microfinance on the poor, a number of studies have found that this sector contributes to the poverty reduction. For the current study, two multiple linear regression models were constructed. Analysis of the results showed that SME lending has a positive effect on the socio-economic development of Kazakhstan. However, the results also showed that as the proportion of poor people increases, the level of bank lending decreases, while the level of MFI lending increases. Thus, MFIs continue to lend to the economy of Kazakhstan, even despite the decrease in the solvency of entrepreneurs, which is fully consistent with the concept of microfinance. Thus, there is a need for the full inclusion of MFIs in the country’s financial system, as well as the expansion of financial services provided by these organizations. Key words: microfinance, microfinance organizations, entrepreneurship, small and medium business (SME), lending, human development index (HDI), poverty index.